Genetic Polymorphisms of Superoxide Dismutase Locus of Pneumocystis jirovecii in Spanish Population - Morilla, Rubén; González-Magaña, Amaia; Friaza, Vicente; de Armas, Yaxsier; Medrano, Francisco J.; Calderón, Enrique J.; de la Horra, Carmen (Frontiers in Public Health, 2019)
Objective: Pneumocystis pneumonia remains a major opportunistic infection in immunocompromised patients worldwide. Colonization with P. jirovecii has recently gained attention as an important issue for understanding the complete cycle of human Pneumocystis infection. P. jirovecii Superoxide Dismutase (SOD) gene could be a molecular target with high clinical relevance, but the epidemiological information about SOD genotypes distribution is scarce. The aim of this work was to provide information about the prevalence of genotypes of Pneumocystis SOD among Spanish patients and to describe possible differences between colonized and PcP patients. Methods: we developed a cross-sectional study analyzing broncho-alveolar lavage fluid samples from 30 Pneumocystis pneumonia patients, 30 colonized patients and 20 controls using a nested PCR protocol designed to amplify the sodA gene of P. jirovecii. The diagnostic yield of SOD Nested PCR was evaluated against the routine practice of mtLSUrRNA Nested PCR, which is considered the gold standard. Results: SOD locus was amplified in 90% of Pneumocystis pneumonia patients, 10% of colonized patients and none of controls. Genotype SOD1 was observed in 11 cases (52.4%) and genotype SOD2 in 10 cases (47.6%). Genotype SOD2 was observed only in Pneumocystis pneumonia patients while the genotype SOD1 was observed in both colonized and Pneumocystis pneumonia patients. Conclusions: This study provides epidemiological information about SOD genotypes distribution in Spain, showing a low genetic diversity and a predominant presence of genotype SOD1 in colonized patients. SOP Nested PCR was more sensitive and accurate assay in PcP patients than in colonized individuals.